Beliefs about and intention to learn a foreign language in face-to-face and online settings. Issue 1 (2nd January 2018) - Alhamami, Munassir
ABSTRACT: This mixed-methods study investigates language learners' intention to attend a class and learn a foreign language in face-to-face and online settings using Ajzen's theory of planned behavior (TPB). The data were collected using interviews, questionnaires, and treatments with participants in two groups: a face-to-face language learning (FLL) group ( n = 690) and an online language learning (OLL) group ( n = 296). The results show that language learners' intentions are shaped by their attitudes toward the language-learning environment, the beliefs of people around them, and their beliefs about their abilities to perform in the language-learning environment. Understanding these three factors can help predict students' intentions to engage or not engage in learning a foreign language in online and face-to-face settings. Comparison of the results from both groups suggests that language learners prefer FLL classes to OLL classes. The use of the mixed-methods design helps to investigate language learners' beliefs. Employing Ajzen's TPB also confirms the need to employ different theoretical models when examining language learners' motivation to learn a language.